What maximal urethral closure pressure threshold predicts failure of mid-urethral sling surgery? - Tsia-Shu Lo; Fazlin Harun; Hateeza binti Zakaria; Yiap Loong Tan; Wu-Chiao Hsieh; Aisha Ayash Ayedh Al-Zabidi (Elsevier, 2024)
Objective: Low Maximal Urethral Closure Pressure (MUCP) is linked to unfavourable outcome of anti-incontinence surgery, however the cut-off value varied within studies. This study aimed to predict the cut-off value of MUCP that contributes to poor outcome of Mid-Urethral Sling (MUS) surgery in Urinary Stress Incontinence (USI) patients. Materials and methods: Records of 729 women underwent MUS procedure from January 2004 to April 2017 reviewed. Patients were divided into four MUCP groups, which were <20 cmH2O (≥20 and < 40) cmH2O (≥40 and ≤ 60) cmH2O and >60 cmH2O. Objective evaluation comprising 72-h voiding diary, multichannel urodynamic study (UDS) and post-operative bladder neck angle measurement. Subjective evaluation through validated urinary symptoms questionnaires. Primary outcome was objective cure rate of negative urine leak on provocative filling cystometry and 1-h pad test weight <2 g, and subjective cure rate was negative response to question 3 of UDI-6. Secondary outcome was identifying risk factors of cure failure for MUS in low MUCP groups. To identify the risk factors of cure failure, MUCP groups were narrowed down into <40 cmH2O or ≥40 cmH2O. Results: Total of 688 women evaluated. Overall objective cure rate was 88.2% with subjective cure rate of 85.9%. Objective and subjective cure rates were lower in groups with low MUCP <40 cmH2O. Failure of MUS correlate significantly in patients with low MUCP <40 cmH20, bladder neck angle <30° and Functional urethral length (FUL) < 2 cm. Conclusion: Women with MUCP <40cmH2O, bladder neck angle <30° and FUL < 2 cm are more likely to have unfavorable outcome following MUS surgery. We proposed the cut-off low MUCP <40cmH2O as predictor for fail MUS surgery in SUI patients.